[Black speaker at a podium in University Union plaza] (1995)
The speaker is wearing a black blazer and sunglasses, and they are holding a microphone on its stand. The blazer has a patch with the initials 'WW' on it, and a red and green ribbon is attached to the speaker's lapel. There are three students behind them on stage.